Nursing practice in multiple sclerosis : a core curriculum - Halper, June; Costello, Kathleen; Harris, Colleen (Demos, 2006)
Nursing Practice in Multiple Sclerosis: A Core Curriculum, 2nd Edition was written for nurses preparing to take the MS certification exam given under the auspices of the International Organization of Multiple Sclerosis Nurses (IOMSN), and for everyone involved, or becoming involved, in the field of MS treatment and care. Developed as a companion to Comprehensive Nursing Care in Multiple Sclerosis, 2nd Edition and Advanced Concepts in Multiple Sclerosis Nursing Care, this guide will help readers learn about the history of MS, its diagnosis, management, and current theories regarding the immunologic basis for the disease.